Luc Tuymans : Exhibitions at David Zwirner 1994-2012 - Temkin, Ann. (Antwerpen : Ludion, 2012)
The David Zwirner Gallery in New York has been the base of operations for Luc Tuymans since 1994. At the start of his career, Tuymans committed himself to showing a new series of works there once every two years - a promise that he has never failed to keep. In the meantime, he has achieved international recognition with his paintings, whose tempered style is combined with an often political content that tackles controversial topics ranging from the Holocaust to the Belgian colonial legacy. This book presents the major works of the artist together with commentary and supplemental materials, plus interviews with Ann Temkin, Brice Marden, Peter Schjeldahl and Robert Storr.
boek